ANALISIS KINERJA KEUANGAN SEBELUM DAN SAAT NEW NORMAL DENGAN PENDEKATAN ALTMAN Z-SCORE PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2017 - 2021 - Kumala, Esti (Taksasila Edukasi Insani, 2023)
This research aims to analyze financial performance before and during the New Normal Using the Altman Z-Score Approach in Property and Real Estate Companies Listed on the IDX in 2017 - 2021.This research is descriptive quantitative research, namely research that systematically and accurately observes problems regarding certain facts and the nature of objects. The population in this research was 81 property and real estate companies registered on the IDX and 5 companies were sampled using the purposive sampling method. The analysis tool uses the Altman Z-Score method to identify companies that are experiencing financial difficulties or financial distress and companies that are in the healthy / non-distress category with certain indicators.The results of this research were obtained from 5 sampling companies studied, there were 4 companies experiencing financial difficulties in the distress category and 1 company was in a healthy/good/non-distress condition in 2017. Meanwhile, in 2018 - 2021, which was the year before the pandemic, during the Covid pandemic -19, and in new normal conditions, 3 companies were still experiencing financial difficulties and 1 company managed to recover from financial difficulties to be in good health/good/non-distress condition, and 1 company was in good health/good/non-distress condition the year before the pandemic , both during the pandemic and after the new normal conditions.Keywords: Altman Z-Score, Financial Difficulty, Covid-19 Pandemic, Financial Performance, Property and Real Estate